Chemical Basis for Qualitative and Quantitative Differences Between ABO Blood Groups and Subgroups: Implications for Organ Transplantation. Issue 10 (26th May 2015) - Jeyakanthan, M.; Tao, K.; Zou, L.; Meloncelli, P. J.; Lowary, T. L.; Suzuki, K.; Boland, D.; Larsen, I.; Burch, M.; Shaw, N.; Beddows, K.; Addonizio, L.; et al.
Abstract : Blood group ABH(O) carbohydrate antigens are carried by precursor structures denoted type I–IV chains, creating unique antigen epitopes that may differ in expression between circulating erythrocytes and vascular endothelial cells. Characterization of such differences is invaluable in many clinical settings including transplantation. Monoclonal antibodies were generated and epitope specificities were characterized against chemically synthesized type I–IV ABH and related glycans. Antigen expression was detected on endomyocardial biopsies (n = 50) and spleen (n = 11) by immunohistochemical staining and on erythrocytes by flow cytometry. On vascular endothelial cells of heart and spleen, only type II–based ABH antigens were expressed; type III/IV structures were not detected. Type II–based ABH were expressed on erythrocytes of all blood groups. Group A1 and A2 erythrocytes additionally expressed type III/IV precursors, whereas group B and O erythrocytes did not. Intensity of A/B antigen expression differed among group A1, A2, A1 B, A2 B and B erythrocytes. On group A2 erythrocytes, type III H structures were largely un‐glycosylated with the terminal "A" sugar α‐GalNAc. Together, these studies define qualitative and quantitative differences in ABH antigen expression between erythrocytes and vascular tissues. These expression profiles have important implications that must be considered in clinical settings of ABO‐incompatible transplantation when interpreting anti‐ABO antibodies measured by hemagglutination assays with reagent erythrocytes. Abstract : ABO(H) blood group antigens are composed of distinct subtype chains that are differentially expressed by erythrocytes used to detect ABO antibodies and cells of transplanted organs, raising important implications regarding interpretation of isohemagglutinin titers for determining suitability for ABO‐incompatible organ transplantation and posttransplant management.